Analysis of Services for Making Electronic Identity Cards at the Department of Residence and Civil Registration - Albertin Barung Mangontan; Abdul Mahsyar; Agus Priyanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Public agencies that issue electronic identity cards nevertheless face several challenges due to limited facilities, staff ability, and access, especially for inhabitants in remote locations far from service centres. This study aims to identify and analyze the service of Electronic ID Card (E-KTP) issuance at the Department of Population and Civil Registration of Tana Toraja Regency, focusing on the quality aspects of service procedures and the existing service technology infrastructure. This research uses a qualitative descriptive method with a case study approach at the Department of Population and Civil Registration (Disdukcapil) of Tana Toraja Regency through in-depth interviews, direct observation, and documentation studies. Data analysis uses Miles and Huberman's interactive model which includes three stages: data reduction, data presentation, and conclusion drawing. The analysis process is carried out continuously to produce a comprehensive understanding of the quality of public services at the Disdukcapil of Tana Toraja Regency. This research shows that the quality of E-KTP services in Tana Toraja Regency has been running well according to Standard Operating Procedures, with a service flow starting from taking queue numbers to printing and receiving E-KTPs. The service is supported by adequate facilities and process transparency. Digital innovations such as recording and printing E-KTPs in eight sub-districts facilitate access for residents in remote areas. The infrastructure and service technologies are good, but outdated hardware, inconsistent internet access at peak hours, and central government form delivery delays limit them. Form collection in Makassar is being done directly to speed up services.